The Rough Guide to cloud computing - Buckley, Peter (London Rough Guides Distributed by the Penguin Group, 2010)
"The Rough Guide to Cloud Computing" is your essential "how to" guide for taking your life online, teaching you how to use online tools to become more productive, find new ways to work and, of course, play. Covers Google Docs, Zoho Office, Twiddla, Flickr, Spotify and Last.fm, Remember The Milk, and Evernote
Twenty years from now we will wonder how we managed in the days before all our documents, bookmarks, emails applications and music were available from anywhere, from any device, 24-7. That's what cloud computing is all about: being creative, being entertained and being organized in an ever-changing digital age
Cloud basics. FAQs : frequently asked questions ; The cloud : from home ; The cloud : going mobile ; Security & safety ; Staying in sync -- Life in the cloud. Staying in touch ; Contacts & calendars ; To-do lists ; Social bookmarks ; Online storage -- Work in the cloud. Online desktops ; Office suites & tools ; Messing with images ; Notes & scrapbooks -- Play in the cloud. Cloud music & video ; Photo clouds ; Social networks ; Maps & more
Includes bibliographical references and index
1 13 14
GENR_KNOWL, NEW
Keywords: Cloud computing; Electronic data processing -- Distributed processing; Web services